FOXO1 Mediates RANKL Induced Osteoclast Formation and Activity - Wang, Yu (J Immunol, 2015)
We have previously shown that the transcription factor FOXO1 is elevated in conditions with high levels of bone resorption. To investigate the role of FOXO1 in the formation of osteoclasts we examined mice with lineage specific deletion of FOXO1 in osteoclast precursors and by knockdown of FOXO1 with siRNA. The receptor activator of NF-kappa B ligand (RANKL), a principal bone resorbing factor, induced FOXO1 expression and nuclear localization two days after stimulation in bone marrow macrophages (BMMs) and RAW264.7 osteoclast precursors. RANKL- induced osteoclast formation and osteoclast activity was reduced in half in vivo and in vitro with lineage specific FOXO1 deletion (LyzM.Cre(+)FOXO1(L/L)) compared to matched controls (LyzM.Cre(−)FOXO1(L/L)). Similar results were obtained by knockdown of FOXO1 in RAW264.7 cells. Moreover, FOXO1-mediated osteoclast formation was linked to regulation of NFATc1 nuclear localization and expression as well as a number of downstream factors including dendritic cell-specific transmembrane protein (DC-STAMP), ATP6vod2, cathepsin K and integrin αν Lastly, FOXO1 deletion reduced M-CSF induced RANK expression and migration of osteoclast precursors. Studies presented here provide the evidence that FOXO1 plays a direct role in osteoclast formation by mediating the effect of RANKL on NFATc1 and several downstream effectors. This is likely to be significant since FOXO1 and RANKL are elevated in osteolytic conditions.